Proneness of accidents among lorry drivers in Malaysia, 1997 the control program at Institute of Respiratory Medicine , Kuala Lumpur, 1998 - Zanariah Ariffin; Md. Idris Mohd Nor (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Currently, road traffic accident has been one of the major public health problem in Malaysia. A prevalence study has been conducted with the objective to find out factors influence proneness of accident among lorry drivers in Malaysia. A total of 268 respondents had been selected using systematic random sampling method. Tests using Chi Square and compare means were used to find out the relation between proneness to accident and the factors being studied. Logistic regression was also used to eliminate influence of major factors in proneness to accident. Results showed 79.9% of the lorry drivers were prone to accident and 39.9% of the respondents has had history of road traffic accident. Drivers who had extravert personality trait, no housing problem and problem with other workers were found to have a significant relation with proneness to accident (p<0.05%). Accident history was also found to have a significant relation to neuroticism and lie / conformity (p<0.05). Extraverts and neuroticism were positively correlated with proneness to accident (r=0.24, p<0.05; 4=0.21, p<0.05). From logistic regression analysis, no housing problem and problem with subordinate were the main factors influencing proneness to accident with odds ratio of 0.77.